Analisis Strategi Pengembangan Sistem Informasi pada PT. Gunanusa Eramandiri dengan Metode Enterprise Architecture - Roy Kurniawan (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The purpose of this study was to analyze the needs of the enterprise information system in order to submit a proposed information systems strategy. Research methods used in this research is the analysis of the Enterprise Architecture. The proposed planning is business strategy planning and information technologysystems in companies, which can be used within a period of several years. The conclusion from this study is that the proposed planning system can help the company's performance in running business processes, and create a competitive advantage for the company to stay afloat and ahead of the stiff competition in the present or in the future.